"Protect Your Loved Ones From Fataki": Discouraging Cross-Generational Sex in Tanzania. (June 2016) - Kaufman, Michelle R.; Tsang, Samantha W.; Mooney, Alyssa; McCartney-Melstad, Anna; Mushi, Adiel K.; Kamala, Benjamin
The Fataki campaign aired in Tanzania via radio from 2008 to 2011 to address cross-generational sex, a major driver of HIV in the region. The campaign sought to incite social disapproval of men who engage in such relationships, generate dialogue around the issue, and encourage community interventions in these relationships through social learning. Using qualitative methods, we explored campaign reactions, use of the term Fataki to describe men in relationships with much younger women, and the nature of discussions spurred by the campaign. We conducted focus group discussions and individual interviews in Iringa and Pwani regions with young women, older men, and community leaders. Results showed that the Fataki term was widely used and had negative connotations reflecting social disapproval of men who participate in such relationships. Dialogue spurred by the campaign, primarily directed toward young women, focused on reasons for avoiding these relationships. We conclude with suggestions for relevant future interventions.